CAL/CALLIOPE’S UNDOING GENDER IN JEFRREY EUGENIDES’MIDDLESEX - ISMI FIRDIANY (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2016)
Abstrak Skripsi ini fokus pada permasalahan undoing gender, karakter utama memiliki kelamin ganda. Masyarakat masih menganggap bahwa fenomena gender yang terjadi kepada seseorang yang mengalami intersex menjadi sebuah permasalahan gender di berbagai aspek masyarakat. Sebagian masyarakat menilai intersex adalah sebuah gangguan. Menurut konsep Judith Butler tentang undoing gender, permasalah utama adalah konsep gender dalam masyarakat. Jenis kelamin adalah sebuah wacana gender yang dibuat oleh itu sendiri. Sehingga manusia yang memiliki dua gender dalam satu tubuh mengalami ketidakstabilan gender, mereka dituntut untuk menampilkan gender sesuai dengan performa mereka. Masalah utama yang diangkat oleh penulis adalah : (1) Bagaimana gender Cal/Calliope terbentuk didalam novel Middlesex oleh Jeffrey Eugenides? (2) Bagaimana undoing gender terjadi kepada Cal/Calliope didalam novel Middlesex oleh Jeffrey Eugenides?. Penulis menggunakan teori Judith Butler tentang Undoing Gender untuk menjelaskan fenomena yang terjadi pada Cal/Calliope. Selain itu penulis menggunakan teori performance and performartivity untuk mendukung teori utama. Hasil dari analisis penulis adalah Cal/Calliope tetap mempertahankan kondisi intersex karena gender adalah sebuah wacana Cal/Calliope memilihi tidak menuruti norma masyrakat yang menilai manusia dari performanya. Sehingga Cal/Calliope memilih jenis kelamin laki-laki. Kata Kunci: jenis kelamin, gender, intersex, undoing gender, performance dan performrtivity Abstract This thesis focus on the undoing gender in the main character who has double sexes. The phenomenon of gender issues that still regard the people as the intersex is gender problem in many aspect in society. Most of people still judge the intersex as a disorder.. According to Judith Butler’s concept of undoing gender, the main case of this problem is gender, while gender is a discourse. If gender, for singular sexual genital subject, is unstable, thus for intersex the gender’s instability precisely goes to be reinforced because the subject has to perform two genders as the result of two sexes in one body as it is exposed in Jeffrey Eugenides’ Middlesex. Looking at this case, the analysis of this thesis is grounded on these two main questions: (1) How is Cal/Calliope gender can be formed depicted in Jeffrey Eugenides’ Middlesex? (2) How does undoing gender happen in Cal/Calliope as reflected in Jeffrey Eugenides’ Middlesex?.The analysis data of this thesis taken from the novel, and using Undoing Gender theory which analyzes Cal/Calliope’s gender in society. Beside, the performance and performartivity approach support to analyze Cal/Calliope to stays in his/her intersex condition. The result of analysis proved that both sex and gender are discourse. The way Cal/Calliope receives two discourses of gender is caused by two sexes in one body, it means he/she will understand of how to become woman and man, therefore an intersex strengthens that gender is unstable as it is performed and it can be undone. It means that Cal/Calliope has undo the gender construction by the way he/she rejects to be like what social norm wants; neither becoming woman and man, he/she remains silent of this construction, and he/she stays in intersex condition. Keywords: sex, gender, intersex, undoing gender, performance dan performrtivity.